Problems in the implementation of modern mathematics in some selected elementary schools of Quezon City - Talukdar, Kamaluddin Ahmad 1935- (1967)
This paper attempted to study the problems and difficulties encountered in introducing modern mathematics into thew curriculum of some elementary schools in Quezon City. Two sets of questionnaires were constructed for the mathematics teachers and for the pupils. To have an overall idea of the modern mathematics program, teacher interviews, class observations and documentary analysis were also done. It was concluded that the authority needs more attention to orient the teachers with methods and contents in modern math. Majority of the people support the philosophy of modern mathematics but a shortage of materials has become a major problem in its implementation. Proper training of teachers is required to gain a positive attitude towards modern mathematics.